If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = -4t Solving 13 = -4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4t' to each side of the equation. 13 + 4t = -4t + 4t Combine like terms: -4t + 4t = 0 13 + 4t = 0 Add '-13' to each side of the equation. 13 + -13 + 4t = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 4t = 0 + -13 4t = 0 + -13 Combine like terms: 0 + -13 = -13 4t = -13 Divide each side by '4'. t = -3.25 Simplifying t = -3.25
| 4a-8whena=6 | | (5+4)[3+(8+5)]= | | 5z-13=-4z+14 | | 3x+12=6x-9x-12 | | 4(8-d)-50=20d-6(3+4d) | | y=sqrt(18x+9) | | 7x-2(x-6)=3 | | 3x+2=5y | | 4(x-5)+11=3(x+2)-3 | | 5(x+0.4)=5 | | 5x+11+119=180 | | 7(2x-1)=3 | | 3+13=2x | | y=5x+11+119 | | -12(3x+5)= | | 2.1x+55.9=10.0-13.2x | | 10x=5(x-11) | | -59-2x=13-10 | | 3n+(1-n)-n=-6 | | 45z-90z= | | 6x[5x-7]=432 | | x+1=44 | | 13-9x=51-2x | | 7a+9b= | | 3(a-2)+5w=22 | | 2x^3+5x^2-12=0 | | -19-9x=10x+23 | | 3m+4-9m=-9-6m+23 | | 16x-8=14x+4 | | 3(3+6x)-3=114 | | 6-68= | | 68-6= |